Global Innovation Contests - Elias Dinopoulos; Constantinos Syropoulos; Theofanis Tsoulouhas (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper develops a two-country, dynamic general equilibrium model with innovation contests to study the impact of globalization on the skill premium and fully-endogenous growth. Higher quality products are endogenously discovered through stochastic and sequential global innovation contests in which challengers devote resources to R&D to discover new products while technology leaders undertake rent-protection activities (RPAs) to prolong the expected duration of their temporary monopoly power by hindering the R&D effort of challengers. The model generates intra-sectoral trade, multinationals, and international outsourcing of investment services. Globalization, captured by a move from autarky to the integrated-world equilibrium, leads to convergence of wages and growth rates. Globalization and long-run growth are either substitutes or complements depending on a country's relative skill abundance and the ranking of skill intensities between RPAs and R&D services. Trade openness between two countries that possess identical relative skill endowments but differ in size does not affect either country's long-run growth.
Keywords: F10; F30; F40; 330; innovation contests; economic growth; scale effects; R&D; rent-protection activities; barriers to innovation; wage premium